Premonitory Awareness Facilitates Tic Suppression: Subscales of the Premonitory Urge for Tics Scale and a New Self-Report Questionnaire for Tic-Associated Sensations - Matsuda, Natsumi; Nonaka, Maiko; Kono, Toshiaki; Fujio, Miyuki; Nobuyoshi, Marina; Kano, Yukiko (Frontiers in Psychiatry, 2020)
Awareness of premonitory urge in Tourette Syndrome (TS) may facilitate tic suppression; however, previous studies have not supported this observation. We aimed to clarify the relationship between tic-associated sensation and tic suppression by identifying the subtypes of tic-associated sensations, including the Premonitory Urge for Tics Scale (PUTS). We developed a new questionnaire called "Rumination and Awareness Scale for Tic-associated sensations" (RASTS) to assess the two additional aspects of tic-associated sensations: the intensity of somatosensory hyperawareness and the ability to identify signals of emerging tics. Sixty-two individuals with TS participated in the study (mean age = 19.1 ± 10.3 years). All participants completed the RASTS, PUTS, and Tic Suppression Scale. Of all participants, 41 were evaluated by the Yale Global Tic Severity Scale (YGTSS), while another group of 41 completed both the Leyton Obsessional Inventory-Child Version (LOI-CV) and the Tics Symptom Self-Report (TSSR). Factor analyses including nine items of the PUTS and the RASTS were conducted, and their relationships with patients’ tic suppression ability were examined. The results support using RASTS for the two supposed dimensions (Rumination about Sensation and Premonitory Awareness) for assessing the two different tic-associated sensations, and PUTS for three dimensions for assessing the two types of quality of premonitory urges and intensity of premonitory urges. Premonitory awareness correlated with tic suppression ability. Conversely, rumination about sensation, PUTS total score, and the three subscales of PUTS correlated with obsessive-compulsive symptoms. In summary, being aware of signals for emerging tics facilitated self-initiated tic suppression, while ruminative tic-associated sensations did not. This study provides new insights into behavioral therapy for tics by identifying two distinct aspects of tic-associated sensations that include premonitory urges.